RETROSPECTIVE ANALYSIS OF DEGENERATIVE LUMBAR SPONDYLOLISTHESIS: TRIGGERING OR AGGRAVATING FACTORS - Rodrigo Arnold Tisot; Juliano da Silveira Vieira; Matheus Backes Sallet; Diego da Silva Collares; Maykon de Oliveira Felippe; Arthur Ascenço Ceolin; Felipe Severo Lanzini; Gabriel Orlandi; João Gabriel de Souza do Canto; Leonardo Cechinato Schio; Lucas Gabriel Mensch da Luz; Luís Henrique Zahner; et al. (Coluna/Columna)
ABSTRACT Objective: Identify and measure probable triggering or aggravating factors of degenerative lumbar spondylolisthesis at the L3-L4 and L4-L5 levels. Methods: This is a cross-sectional study, analyzing medical records of patients surgically treated by a spine surgeon at the Hospital Ortopédico de Passo Fundo, from 2002 to 2020. Results: There was a statistically significant correlation between the degree (p=0.041) and percentage (p=0.046) of slippage with lumbar lordosis. There was also a statistically significant correlation between the percentage of slippage and the severity of disc degeneration (p=0.032). The other analyzed variables did not obtain statistical relevance. Conclusions: The degree and percentage of slippage of Degenerative Lumbar Spondylolisthesis were more pronounced in patients with greater lumbar lordosis. The percentage of slippage was also more pronounced in patients with greater disc degeneration. Level of Evidence III; Retrospective Study.